Analisis Tingkat Pengangguran Di Daerah Provinsi Banten Akibat Pandemi Covid-19 Tahun 2021 - Alfiana, Salma; Ramadaneta, Tiara Frisach; Oktafiani, Dini; Putri, Gabriella Stephanie Regina; Kencana, Adjie Restu; Desmawan, Deris (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
The Covid-19 pandemic has had a significant impact on the global economy, including Indonesia, Banten Province being one of the areas affected, with an increase in the unemployment rate as one indicator. The purpose of this study was to analyze the unemployment rate in the Banten area due to the Covid-19 pandemic. This study used a qualitative approach or secondary data method from the Central Bureau of Statistics (BPS) and analyzed using linear regression. The results of the study show that the unemployment rate in Banten has increased significantly since the Covid-19 Pandemic began. This is due to the reduced number of jobs and a decrease in economic activity in the area. This research is expected to contribute to the development of government policies in overcoming the effects of the Covid-19 Pandemic on the unemployment rate in Banten Province.